Oxidative stress associated with pathological changes in the pancreas of cattle naturally infected by Eurytrema coelomaticum - Schwertz C.I. (2016)
© 2016 .Although Eurytrema coelomaticum is considered a parasite with low pathogenicity, it may be associated with mortality and loss of productive performance in animals due to chronic pancreatitis. The aim of this study was to evaluate the occurrence of oxidative stress caused by E. coelomaticum in naturally infected cattle, correlating the biochemical findings with the parasite load and histopathological changes. For this study, blood and pancreas samples from 51 cattle were collected, and levels of the thiobarbituric acid reactive substances (TBARS), advanced oxidation protein products (AOPP) and ferric reducing ability of plasma (FRAP) were measured in the serum and pancreas, and superoxide dismutase (SOD) activity was measured in total blood. Parasite burden was determined opening the pancreatic ducts, and then fragments of pancreas were collected and fixed in 10% buffered formalin and routinely processed for histopathology. From the 51 collected pancreas, 33 (63.5%) were parasitized. The average parasite burden per pancreas was 532 (12-2,578). TBARS and FRAP showed higher levels in serum and pancreas of infected animals (p < 0.05), with a positive correlation between the histopathological changes and the number of parasites. SOD level in blood was 42% higher in parasitized group compared with control group (p < 0.05), as well as AOPP in serum. Based on these results, we concluded that in natural infection by E. coelomaticum in cattle, oxidative stress occurs, characterized by the occurrence of protein oxidation, lipid peroxidation and activation of antioxidant system.